Variability in Medullary Thyroid Carcinoma in RET L790F Carriers: A Case Comparison Study of Index Patients - Mathiesen, Jes Sloth; Nielsen, Søren Grønlund; Rasmussen, Åse Krogh; Kiss, Katalin; Wadt, Karin; Hermann, Anne Pernille; Nielsen, Morten Frost; Larsen, Stine Rosenkilde; Brusgaard, Klaus; Frederiksen, Anja Lisbeth; Godballe, Christian; Rossing, Maria (Frontiers in Endocrinology, 2020)
BACKGROUND: Previous studies have suggested that the variability in age of onset and aggressiveness of medullary thyroid carcinoma (MTC) in patients with multiple endocrine neoplasia type 2A (MEN 2A) carrying the same REarranged during Transfection (RET) mutation may be caused by additional RET germline variants or somatic variants. METHODS: This study was a retrospective case comparison study of all MEN 2A index patients (n=2) with the RET L790F germline mutation in Denmark. Whole blood and MTC tissue were analysed for RET germline variants and other somatic variants (>500), respectively. RESULTS: Patient 1 presented with MTC (T1aN1bM0) at age 14 years, while patient 2 presented with MTC (T1bN0M0) at age 70 years. No germline RET germline variants nor other variants were found to explain this MTC variability. CONCLUSIONS: We could not confirm the previously reported finding of a somatic RET variant as likely responsible for the early onset and aggressiveness of MTC in a RET germline mutation carrier. Also, we found no RET germline variants that could explain the MTC variability among our index patients. We did, however, identify a somatic FLT3 R387Q variant with an unknown potential as genetic modifier.